Primary pulmonary botryomycosis: a late complication of foreign body aspiration. Issue 12 (1st December 2000) - Tuggey, J M; Hosker, H S R; DaCosta, P
Abstract : Primary pulmonary botryomycosis is a rare cause of haemoptysis and can enter the differential diagnosis of a mass on the plain chest radiograph. The case history is presented of a 63 year old man with botryomycosis which was initially thought to be a bronchial carcinoma. When the diagnosis was made several years later it was found to be secondary to persisting vegetable material in the bronchial tree following previous aspiration.